Chemotherapy near the end of life; assessment of the clinical practise in onco-hematological in adult patients - Pilar Taberner Bonastre; María Teresa Taberner Bonastre; Enrique Soler Company; María Dolores Pérez-Serrano Lainosa (Farmacia Hospitalaria)
Objective: ensure a good quality of life in the last phase of onco- hematological patients should be the primary goal, despite this, we have little data at European level and published studies are contradictory. Nevertheless, most of them agree saying that administrating chemotherapy near the end of life impacts negatively in the patients quality of life. The main objective of this study is to analyze the treatment non-aggressiveness parameters in onco-hematological patients. The secondary objective is to do a describing study of the clinical variables of the patients who receive chemotherapy at the end of life and the treatments more used. Methods: a retrospective observational study was conducted in a tertiary hospital. Both, oncological and hematological patients receiving chemotherapy (oral or intravenous) between January and December 2013 who were receiving chemotherapy in the last 90 days before death, were included. Results: there were 823 patients that were threated between January and December of 2013. Of these 106 (13%) met the inclusion criteria to be analyzed. There were a 14.1% (n = 93) of oncological and a 8.4% (n = 13) of hematologic patients that maintained the antineoplasic treatment during the last three months before death. A 21.7% (n = 23) of the patients received chemotherapy in the last two weeks of life, 41.5% (n = 44) in the last 30 days and 78.3% (n = 83) in the last two months of life. There was a 67.9% (n = 72) of patients that had hospital admissions during their last three months of life, 47,2% (n = 50) during the last month, 33% (n = 35) during the last two weeks and 10,4% (n = 11) during the last three days of life. A 25,5% (n = 27) of patients had more than one hospital admission during their last 90 days. Conclusions: according to the Earle et al. criteria, our population had been treated aggressively. We need more scientific evidence with consolidate date that allows us to establish a unified criteria for the selection of patients with advanced cancer who may benefit from receiving antineoplasic treatments